The Mesolithic Hunter–Gatherer Camp Site at Sammakko in Norrbotten, Northernmost Sweden—Archeological Finds and Palaeoenvironmental Reconstruction - Möller, Per; Palmbo, Frida; Nielsen, Anne Birgitte; Boman, Emma; Dong, Haoran; Björck, Svante; Cai, Yuanyang; Grimbe, Jannica; Macleod, Ruairidh; Shen, Mingjian; Wang, Yucheng; Westerlund, Mica; et al. (Wiley, 2024)
Publication status: Published Funder: This work was funded by the County Administrative Board of Norrbotten and the Göran Gustafsson Foundation. SedaDNA work was supported by the NSFC BSCTPES project (No. 41988101) and the Carlsberg Foundation (CF18‐0024). ABSTRACT A small Mesolithic camp site near Sammakko in northernmost Sweden has been identified through its abundance of burnt bone and quartz refuse from stone tool manufacturing/maintenance. Radiocarbon dating places hunter–gatherer activity here around 8900 years ago, 1800 years later than the oldest known settlement in Norrbotten, the Aareavaara site. Sediment stratigraphy in nearby lake basins suggests that the final melting of stagnant ice, trapped in the undulating Veiki‐moraine landscape, occurred around 9200 years ago. Initially, after deglaciation, the area was covered with arctic heath, transitioning to an open birch forest by 9100 years ago. At the time of the Sammakko settlers, it was an open birch forest with elements of pine, and various dwarf shrubs, including dwarf birch, willow, and juniper. Grasses, sedges, and various herbs in the semi‐open grounds were also common. The settlers primarily relied on reindeer, as indicated by burnt bones, with supplementary food sources such as pike and birds. Stalking was likely the main hunting method, possibly aided by dogs. Potential dog gnaw marks on bones suggest early domestication. The site functioned as a temporary hunting station, probably used only during snow‐free months.